Megadroughts and pluvials in southwest Australia: 1350–2017 CE - Alison J. O’Donnell; W. Lachlan McCaw; Edward R. Cook; Pauline F. Grierson (Climate Dynamics, 2021)
Declining winter rainfall coupled with recent prolonged drought poses significant risks to water resources and agriculture across southern Australia. While rainfall declines over recent decades are largely consistent with modelled climate change scenarios, particularly for southwest Australia, the significance of these declines is yet to be assessed within the context of long-term hydroclimatic variability. Here, we present a new 668-year (1350–2017 CE) tree-ring reconstruction of autumn–winter rainfall over inland southwest Australia. This record reveals that a recent decline in rainfall over inland southwest Australia (since 2000 CE) is not unusual in terms of either magnitude or duration relative to rainfall variability over the last seven centuries. Drought periods of greater magnitude and duration than those in the instrumental record occurred prior to 1900 CE, including two ‘megadroughts’ of > 30 years duration in the eighteenth and nineteenth centuries. By contrast, the wettest > decadal periods of the last seven centuries occurred after 1900 CE, making the twentieth century the wettest of the last seven centuries. We conclude that the instrumental rainfall record (since ~ 1900 CE) does not capture the full scale of natural hydroclimatic variability for inland southwest Australia and that the risk of prolonged droughts in the region is likely much higher than currently estimated.